EPR, Magnetic, and Computational Characterization of Linear and Zigzag Ladder‐type Chains of Exchange Coupled Cu(II) Complexes with Picolinic and Dipicolinic Acid Ligands - Pérez, Ana Laura (2021)
We report magnetic, EPR, and computational studies on two representative examples of structurally well-characterized one dimension (1D) molecular systems: the copper complexes catena-[bis(μ-pyridine-2-carboxylato)-copper dihydrate] and catena-[(μ2-pyridine-2,6-dicarboxylato)-diaqua-copper(II)], hereafter 1 and 2, respectively. Experimental and theoretical results confirmed that the structural chains in both compounds behave as magnetic chains in which the copper ions are weakly coupled by isotropic exchange. Magnetic susceptibility measurements of 1 suggested that the copper ions are antiferromagnetically coupled whereas EPR measurements suggested ferromagnetic coupling at temperature above 100 K which becomes antiferromagnetic at low temperatures. Computational calculations would indicate that the ferromagnetic-antiferromagnetic change may be due to dCu−Oap shortening on lowering temperature temperature (a fact that was observed experimentally by XRD at low temperatures), which redistributes the small Cu(II) unpaired spin density delocalized on the apical ligand to copper. The 1D magnetic behavior of the zigzag ladder chain of 2 is less detectable than that of the single chain of 1. Magnetic susceptibility measurements in conjunction with computational calculations showed that the pathways that give rise to the 1D ladder transmit ferromagnetic exchange interactions with different strengths, with the stronger interaction being transmitted along the rungs. The role of the weaker exchange interactions transmitted along the rails on the magnetic dimensionality of 2 is analyzed.